2021
DOI: 10.1038/s41598-021-91589-2
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term outcome of intravitreal anti-vascular endothelial growth factor treatment for pachychoroid neovasculopathy

Abstract: To compare the long-term effectiveness of intravitreal anti-vascular endothelial growth factor (VEGF) treatment for pachychoroid neovasculopathy (PNV), polypoidal choroidal vasculopathy/aneurysmal type 1 neovascularization (PCV/AT1), and typical neovascular age-related macular degeneration (nAMD). Forty-one eyes with PNV, 68 eyes with PCV/AT1, and 56 eyes with typical nAMD were retrospectively included for analysis. All patients were treatment-naïve and received a three-monthly loading injection of anti-VEGF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although this study did not deny the inclusion of eyes with polypoidal lesions in PNV, another study on PNV from South Korea excluded eyes with polypoidal lesions from PNV, based on their understanding that type 1 CNV with polypoidal lesions should be classified as PCV [ 73 ]. Later studies from Korea have also considered PNV without polypoidal lesions as PNV and PNV with polypoidal lesions as PCV [ 74 , 75 , 76 , 77 ]. In Europe, an Italian study group included eyes with polypoidal lesions in PNV [ 78 ], whereas study groups from Germany and Turkey excluded eyes with polypoidal lesions from PNV [ 79 , 80 , 81 , 82 , 83 ].…”
Section: Establishment Of the Pachychoroid Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study did not deny the inclusion of eyes with polypoidal lesions in PNV, another study on PNV from South Korea excluded eyes with polypoidal lesions from PNV, based on their understanding that type 1 CNV with polypoidal lesions should be classified as PCV [ 73 ]. Later studies from Korea have also considered PNV without polypoidal lesions as PNV and PNV with polypoidal lesions as PCV [ 74 , 75 , 76 , 77 ]. In Europe, an Italian study group included eyes with polypoidal lesions in PNV [ 78 ], whereas study groups from Germany and Turkey excluded eyes with polypoidal lesions from PNV [ 79 , 80 , 81 , 82 , 83 ].…”
Section: Establishment Of the Pachychoroid Conceptmentioning
confidence: 99%
“…To date, only one group from South Korea compared PNV and nAMD by excluding eyes with polypoidal lesions from the studied cohorts ( Table 9 ). This group suggested no clear difference in fluid control and visual acuity change after anti-VEGF treatment for PNV and nAMD [ 72 , 77 ]. Other studies on PNV without polypoidal lesions have reported that PDT and anti-VEGF treatment were effective for PNV without polypoidal lesions [ 64 , 65 , 66 , 73 , 80 , 81 , 85 , 86 ].…”
Section: Treatment Response Of Pnvmentioning
confidence: 99%
“…In the present study, macular atrophy developed in some patients of each group with a comparable incidence. Yoon et al reported that 3-year incidence of macular atrophy was 9.8%, that was smaller than typical AMD [ 26 ]. The result of the present study showed similar incidence (7%).…”
Section: Discussionmentioning
confidence: 99%
“…38 PNV requires a fewer number of injections than neovascular age-related macular degeneration, with longer treatmentfree period of up to 36 months. 39,40 PDT of various dosage and fluence is effective on improving visual acuity, central macular thickness, and choroidal thickness. 26,30 PDT enables fluid absorption in patients non-responsive to anti-VEGF.…”
Section: Pachychoroid Neovasculopathymentioning
confidence: 99%